Primary Cutaneous Malignant Perivascular Epithelioid Cell Tumor Mimicking Undifferentiated Pleomorphic Sarcoma: A Report of a Rare Entity. (2nd October 2022) - Neumann, Neil M.; Cornelia Ding, Chien-Kuang; Borgen, Amanda; Corvera, Carlos U.; North, Jeffrey P.; Qorbani, Amir; Horvai, Andrew E.
Abstract: Primary cutaneous malignant perivascular epithelioid cell tumor (PEComa) is a rare and potentially aggressive neoplasm. In this article, we report the case of a 34-year-old man who initially presented with a 3-cm mass involving the skin and soft tissue of the right shoulder that, over 3 months, enlarged to 12 cm. Histologic examination of the mass revealed an infiltrative neoplasm with features resembling an undifferentiated pleomorphic sarcoma, including sheets of pleomorphic cells with abundant atypical mitoses and necrosis. Immunohistochemical evaluation showed features suggestive of PEComa. Next-generation sequencing revealed pathogenic homozygous deletions of TSC2 and TP53 genes and numerous large-scale copy number changes. Taken together, the findings supported malignant PEComa. This case demonstrates only the seventh example of malignant cutaneous PEComa. Although cutaneous PEComa is chiefly a benign mesenchymal neoplasm, in rare cases, it can rapidly transform into a malignant and infiltrative sarcoma, requiring prompt surgical management.